2006
DOI: 10.1016/j.jpainsymman.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability and Symptom Outcomes Associated with l-Carnitine Supplementation in Patients with Cancer, Fatigue, and Carnitine Deficiency: A Phase I/II Study

Abstract: Carnitine deficiency is among the many metabolic disturbances that may contribute to fatigue in patients with cancer. Administration of exogenous L-carnitine may hold promise as a treatment for this common symptom. Little is known about L-carnitine safety, tolerability, and dose-response in patients with cancer. We conducted a Phase I/II open-label trial to assess the safety and tolerability of exogenous L-carnitine and clarify the safe dose range associated with symptom effects for future controlled trials. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 14 publications
1
69
1
3
Order By: Relevance
“…18 Other studies have confirmed L-carnitine's safety at dosages of 2000mg per day. 19 In these investigations mild adverse events, including nausea and stomach discomfort were noted. Uncommon side effects included muscle weakness in uremic patients and seizures in those with known seizure disorders.…”
Section: Case #3mentioning
confidence: 85%
“…18 Other studies have confirmed L-carnitine's safety at dosages of 2000mg per day. 19 In these investigations mild adverse events, including nausea and stomach discomfort were noted. Uncommon side effects included muscle weakness in uremic patients and seizures in those with known seizure disorders.…”
Section: Case #3mentioning
confidence: 85%
“…No patient experienced significant side effects and no toxicities were noted. These findings suggest that ALC may be safely administered at doses up to 3000 mg where positive effects may be more likely to occur at [129]. Treatments for cancer-related fatigue with an aim to develop directions for future research in large, randomized clinical trials [130].…”
Section: Acetyl-l-carnitinementioning
confidence: 98%
“…Serum carnitine measures included total carnitine, free carnitine, acyl: free carnitine ratio ((total-free carnitine)/ free carnitine), and the prevalence of carnitine deficiency as defined by free carnitine (<35 μmol/L for males and <25 μmol/L for females) and acyl: free carnitine ratio (>0.40) [14]. Carnitine was analysed using butyl ester derivatives and electro spray tandem mass spectrometry [15].…”
Section: Carnitine Levelsmentioning
confidence: 99%